CREATING SUSTAINABLE ULTRA-HIGH-PERFORMANCE CONCRETE (UHPC) UTILIZING RECYCLED GLASS - Ismaeel A.M.; Usman F.; Hayder G.; Al-Ani Y. (Sciendo, 2025)
Sustainable construction materials and trash reuse are effective ecological remedial solutions. Concrete is widely used in construction and structural applications. Ultra-high-performance concrete (UHPC) is a popular concrete innovation with high mechanical properties. However, Portland cement is used in large quantities, making UHPC expensive and limiting its use in structural engineering. Significant CO2 emissions and natural resource depletion occur. To make UHPC more environmentally friendly and affordable, substitute PC in concrete mixture with several additives. This study uses Ground Granulated Blast Furnace Slag (GGBS) and waste glass (WG) at 0%, 10%, and 20% cement replacement to create an eco-friendly and cost-effective UHPC. To accomplish this, 3 cylinders per mix were made and separated. Experimental tests include slump, UPV, compaction factor, and mechanical characteristics. GGBS and WG improved concrete mix workability, according to the findings. For best workability and mechanical properties, replace 10% of cement with WG and GGBS in concrete. Using 10% material additives as cement replacement decreased concrete compressive and tensile strength. ? Author(s) 2024.